NASIONALISME PESERTA DIDIK SMK NEGERI 2 GORONTALO BERBASIS NILAI-NILAI SEJARAH - Nggilu, Ariyanto (Universitas Negeri Gorontalo, 2023)
History may be the most important component in the learning process, students can understand the struggle of the Indonesian people in achieving independence and the values ​​fought for by national heroes, it also encourages students to be involved in projects related to local or national history. Student involvement in activities related to history and nationality, such as visits to history museums, participation in Independence Day commemorations, or research projects on freedom fighter figures, can increase their awareness of the significance of the struggle. The research method used in this research is Qualitative Research using a Descriptive Approach